Recentivism and the loss of the methapisical sens - Bańka, Józef (Folia Philosophica, 2002)
The subject of the present article is an attempt to outline the theory of transcendental recentivism. Transcendentalism is described here as a passage of the recens moment of being from the inchoative recensial to the parallel recensial which receives the name of the Supermonad. The recens moment of being is characterised by the suddenness of the explosion of the phenomena which later become situated on both sides of that recens. The suddenness of that explosion contributes to the loss, by the existential recensial, of the metaphysical sense.